Accounting regulation changes: differing attitudes of directors and auditors. (1st January 2013) - O'Leary, Conor; Boolaky, Pran; Delaney, Deborah
After the global financial crisis many jurisdictions adjusted or proposed to adjust their accounting regulations, to improve financial reporting frameworks. This study examines and then compares the attitudes of Australian directors and external auditors to proposed legislative changes impacting upon annual reporting requirements. Directors appear opposed to additional legislation and indicate they would be less comfortable in their current roles and may not seek additional board roles. Auditors appear in favour of proposals which increase the responsibilities of preparers and would be more comfortable in their current roles if implemented. However, they appear opposed to additional responsibilities for reviewers of those reports. Directors and auditors were unequivocal in their opposition to any proposals which could impact on audit appointment . This has audit independence implications. The significance of the study is that legislators should consider carefully the impact of proposed accounting regulation changes as the need to balance investors' rights and protections, with directors' and auditors' ability to effectively perform their duties, continues to be a complex balancing act.